2019 IEEE Power &Amp; Energy Society General Meeting (PESGM) 2019
DOI: 10.1109/pesgm40551.2019.8973954
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Wide-Area Measurement-Based Damping Controller for Networks With Embedded Multiterminal and Multiinfeed HVDC Links

Abstract: Many critical industrial control systems integrate a mixture of state-of-the-art and legacy equipment. Legacy installations lack advanced, and often even basic security features, risking entire system security. Existing research primarily focuses on the development of secure protocols for emerging devices or protocol translation proxies for legacy equipment. However, a robust security framework not only needs encryption but also mechanisms to prevent reconnaissance and unauthorized access to industrial devices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Various control techniques have been used to increase the damping ratio to suppress the LFO for power systems, such as power system stabilizers (PSSs) [3][4][5][6], flexible AC transmission systems (FACTSs) [7][8][9], and the additional damping control of HVDC [10,11]. The high controllability and fast response characteristics of HVDC can be used to damp LFO by adding supplementary control on the basis of original control, which was noted in [12][13][14][15][16][17][18][19][20][21][22]. In [12], an additional damping controller for LCC-HVDC provided by the multilevel linear optimal method has the advantages of good adaptability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various control techniques have been used to increase the damping ratio to suppress the LFO for power systems, such as power system stabilizers (PSSs) [3][4][5][6], flexible AC transmission systems (FACTSs) [7][8][9], and the additional damping control of HVDC [10,11]. The high controllability and fast response characteristics of HVDC can be used to damp LFO by adding supplementary control on the basis of original control, which was noted in [12][13][14][15][16][17][18][19][20][21][22]. In [12], an additional damping controller for LCC-HVDC provided by the multilevel linear optimal method has the advantages of good adaptability.…”
Section: Introductionmentioning
confidence: 99%
“…Reference [16] presented a novel combined design of VSC-HVDC and PSS controllers to enhance the damping of the power system. Wide area measurement systems (WAMSs) are increasingly applied in large-scale power systems, so the wide area damping control of HVDC to suppress LFOs has become the subject of considerable attention among many researchers [17][18][19]. In [17], a wide-area multi-HVDC damping controller based on power system state space model identification of auto regressive exogenous was designed to improve damping efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Preece et al [16] demonstrated a controller for POD based on a Linear Quadratic Gaussian regulator by using WAMS. Pierre et al [17] proposed a supervisory controller for inter-area POD by using real-time frequency measurements, while Agnihotri et al [18] designed a robust controller that considered partial and complete loss of communications. These control strategies showed satisfactory performance, but the requirement of fast communication increases the system complexity and reduces reliability [19].…”
Section: Introductionmentioning
confidence: 99%
“…Other authors focused on control strategies for POD by using Wide Area Measurement Signals (WAMS). For example, Pierre et al [15] proposed a supervisory controller for inter-area POD by using real-time frequency measurements, while Agnihotri et al [16] designed a robust controller that considered the loss of communications. These controllers showed satisfactory performance, but the requirement of fast communication reduces the reliability.…”
Section: Introductionmentioning
confidence: 99%